Werner Cuvelier FeliXart Museum, Drogenbos, 22.11.2015-28.2.2016 - Ellias, Willem; Maes, Frank; Servellón, Sergio; Van Canneyt, Hilde (AsaMer, 2015)
This book features the works of Belgian Conceptual artist Werner Cuvelier ( ̊1939). Since the sixties onwards, Cuvelier has been working on a constant and consistent oeuvre that seems to start from the concepts of arrangement, cataloguing and inventories of facts. The book focusses on Cuvelier's impressive and colorful oeuvre , and thanks to many archival pieces and studio views, provides an insightful view into his living and working world.